2017
DOI: 10.1002/agr.21515
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic versus static inefficiency assessment of the Polish meat‐processing industry in the aftermath of the European Union integration and financial crisis

Abstract: This paper assesses the dynamic inefficiency of the Polish meatprocessing industry during the period between 2004 and 2012. This study employs also a comparison of dynamic with static inefficiency measures to address the importance of accounting for adjustment costs when measuring a firm's inefficiency. Dynamic and static cost inefficiencies and their decomposition into technical, allocative, and scale inefficiency are derived using Data Envelopment Analysis (DEA). Results show that firms' low levels of dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Bontemps et al (2012) found technical inefficiency levels for the poultry industry in France that are similar to our findings. Regarding dynamic inefficiency studies of meat processing industry, our results are similar to those of Kapelko (2017b) findings for the meat processing industry in Poland.…”
Section: Dynamic Multi-directional Managerial Inefficiencysupporting
confidence: 80%
“…Bontemps et al (2012) found technical inefficiency levels for the poultry industry in France that are similar to our findings. Regarding dynamic inefficiency studies of meat processing industry, our results are similar to those of Kapelko (2017b) findings for the meat processing industry in Poland.…”
Section: Dynamic Multi-directional Managerial Inefficiencysupporting
confidence: 80%
“…The dynamic inefficiency indicators (cost, technical and allocative inefficiencies) were estimated for each year separately, relative to the metafrontier based on observations of firms in all regions, and to a region‐specific frontier. Following previous literature (e.g., Kapelko et al ., 2014; Dakpo, 2015; Kapelko, 2017), the directional vector used in the computations is g x = x 0 n , n = 1, …, N , for variable inputs and g I = 0.2 K 0 f , f = 1, …, F , for investment. As noted in section 3, we assume CRS technology in our calculations.…”
Section: Resultsmentioning
confidence: 99%
“…The firms’ output are measured as revenues as reported in the firm’s profit and loss accounts. Previous studies on efficiency in the meat processing industry also applied one single output (e.g., Ali, 2007; Keramido et al, 2011; Kapelko, 2017). Fixed assets represent quasi‐fixed inputs; the value of fixed assets in a given year t was measured as the opening value of fixed assets from the firm’s balance sheet.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations